KULTURISASI PENDIDIKAN KARAKTER DALAM PEMBELAJARAN DI SEKOLAH - Nanang Faisol Hadi (IAIN Padangsidimpuan, 2016)
Early childhood is a critical period for the establishment of a person's character. Many education experts say that the failure of character planting earlier can form personal problems in next adult life. Children will grow with characters if they grow up in an environment with character, so that the nature of every child born to develop optimally sacred. As the Prophet Muhammad said, which means: “Every child is born, must have been in a state of purity. Then both his parents who make it Jewish, Christian and Zoroastrian”. (H.R. Imam Muslim). Character education requires as habit. Habituation to do good thing, to be honest, knight, to be shame cheated, lazy, and to let the environment dirty. Character is not formed instantly, but should be trained seriously and proportionate in order to achieve the ideal shape and strength.